Riparian hydraulic gradient and stream‐groundwater exchange dynamics in steep headwater valleys. Issue 2 (6th June 2013) - Voltz, Thomas; Gooseff, Michael; Ward, Adam S.; Singha, Kamini; Fitzgerald, Michael; Wagener, Thorsten
Abstract: [1] Patterns of riparian hydraulic gradients and stream‐groundwater exchange in headwater catchments provide the hydrologic context for important ecological processes. Although the controls are relatively well understood, their dynamics during periods of hydrologic change is not. We investigate riparian hydraulic gradients over three different time scales in two steep, forested, headwater catchments in Oregon (WS01 and WS03) to determine the potential controls of reach‐scale valley slope and cross‐sectional valley geometry. Groundwater and stream stage data collected at high spatial and temporal resolutions over a period encompassing a 1.25 year storm and subsequent seasonal baseflow recession indicate that hydraulic gradients in both riparian aquifers exhibit strong persistence of down‐valley dominance. Responses to rainfall do not support the simple conceptual models of increased riparian hydraulic gradient toward streams. Hydraulic gradient response in WS01 to both the seasonal baseflow recession and the storm suggested the potential for increased stream‐groundwater exchange, but there was less evidence for this in WS03. Results from four constant‐rate tracer injections in each stream showed a high baseline level of exchange overall, and both a slight seasonal increase (WS01) and slight decrease (WS03) in the riparian intrusion of tracer‐labeled stream water as stream discharge receded. These results indicate that steep headwater valley floors host extensive stream water exchange and very little change in the water table gradients over 3 orders of magnitude of stream discharge. Key Points: Riparian water tables did not develop strong stream‐ward gradients during storm Riparian water tables varied little over 3 orders of magnitude stream discharge Stream‐groundwater exchange varied little through baseflow recession